Bimbingan Konseling Multikultural dalam Meningkatkan Toleransi dan Pemahaman Antarbudaya Siswa - Srimuliati Srimuliati; Tari Datu Lapik; Leni Lewi Pongdatu; Utari Sanda Pare; Ronaldo Stefanus (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
This paper discusses the role of multicultural counseling guidance in enhancing students’ tolerance and intercultural understanding within increasingly diverse school environments. The multicultural approach in counseling services is understood as a deliberate effort to acknowledge, appreciate, and facilitate the cultural differences each student brings. Through counseling processes that are sensitive to cultural backgrounds, students are guided to recognize their identity, understand others’ perspectives, and develop the ability to interact constructively across cultural contexts. The study highlights four key areas: strengthening cultural identity awareness, developing intercultural communication skills, preventing and addressing conflicts related to cultural differences, and fostering an inclusive school environment. The discussion shows that multicultural counseling can enhance tolerant attitudes by providing a safe space for students to express their cultural experiences. In addition, this approach helps schools build an atmosphere that respects diversity through collaboration between counselors, teachers, and other stakeholders. These findings affirm that multicultural counseling guidance is an essential component in creating a peaceful school culture that values differences and supports students’ social-emotional development amid the ongoing dynamics of diversity.